The influence of the dialkylphenyltolane's difluorosubstitution on mesomorphic and dielectric properties. Issue 10 (9th August 2018) - Pytlarczyk, Marta; Herman, Jakub; Harmata, Piotr; Urban, Stanisław; Kula, Przemysław
ABSTRACT: The synthesis of variously difluoro-substituted 4-butyl-4ʹ-[2-(4-butylphenyl)ethynyl]-1, 1ʹ-biphenyls is presented and discussed. Molecular correlations between positions of fluorine atoms at phenyltolane core and mesomorphic, dielectric properties of newly synthesised liquid crystals (LC) have been drawn and discussed. New LC molecules exhibit a wide range of nematic phase and are promising components of liquid crystalline mixtures. They were characterised by 1 H NMR spectroscopy and mass spectrometry analysis. Phase transition temperatures, enthalpies, mesomorphic and dielectric properties were confirmed by a polarising optical microscopy, differential scanning calorimetry and dielectric spectroscopy. Graphical Abstract: